Presence of Probst Bundles Indicate White Matter Remodeling in a Dog With Corpus Callosum Hypoplasia and Dysplasia - Wang-Leandro, Adriano; Dennler, Matthias; Beckmann, Katrin M. (Frontiers in Veterinary Science, 2018)
Corpus callosum abnormalities (CCA) rarely occur in dogs and are related to hypo/adypsic hypernatremia and seizures. Hypoplasia and dysplasia of the corpus callosum (CC) with concomitant lobar holoprosencephaly is the most common variant. It is currently uncertain using conventional MRI if canine CCA reflects the failure of commissural fibers to develop or the failure of the commissural fibers to cross hemispheres. Diffusion tensor imaging was performed in a 4-year-old Staffordshire mix breed dog with CCA and an age-matched healthy Beagle. In comparison to the control dog, CC tractography of the affected dog depicted only axonal tracts corresponding to the temporal CC fibers. The cingulum bundles appeared supernumerary with unorganized architecture, extending into the ipsilateral cerebral cortex and therefore strongly suggested homology to Probst bundles reported in humans with CCA. The presence of Probst bundles in canine CCA could represent compensatory neuroplasticity-mediated networking and may contribute the fair prognosis reported in affected dogs.